Kebijakan Antariksa Amerika Serikat Pada Era Presiden Barack Obama (2009-2016): Hegemoni Melalui Private Commercial Spaceflight - Kristanti, Diyan (Global and Policy Journal of International Relations, 2017)
ABSTRACTSpace not only offer scientific benefits but also has the potential of industrial, commercial and social, it is an attraction that emerged since the beginning of the Space Age. Gradual involvement of the private sector is known as the second era. In this second era, the private sector began to offer launch services or the operation of their own space objects. This era also known as futures space is closely related to space tourism activities. Space tourism then can‟t not be separated from the service provider space accommodation. Among the service provider sector trip into space, commonly called commercial human-base spaceflight. The Legal Principles Governing the Activities of States in the Exploration and Use of Outer Space that containe involvement of the private sector should be under the auspices and responsibility of the country concerned, therefore, the necessary regulatory and legal shelter framework. An international model that exists today following the space tourism industry standard that is owned by the United States, called the United States or the Commercial Space Launch Act (CSLA). United States domestic law allows the minister of regulations governing the transport in all activities related to the aerospace industry. The domestic law, namely Law of the National Aeronautics and Space Administration, or called (NAS Act). If related to this study, the authors examine the policy that focuses on the regulation of private commercial spaceflight that emerged in the era of President Barack Obama. Post-issuance of space policy by President Obama, resulting in a rapid growth in the spacecraft industry and flight crew (spaceflight). Further growth of the commercial space transportation industry in the United States seemed to have dominated the commercialization of space activities around the world.Keywords: space policy, space commercialization, private commercial spaceflight, domination.DOI: https://doi.org/10.33005/jgp.v5i02.1886